Phylogeographic Pattern of Sargassum hemiphyllum var. chinense (Phaeophyceae, Ochrophyta) in Chinese Coastal Waters - Zepan Chen; Weizhou Chen; Hong Du (Plants)
Sargassum hemiphyllum var. chinense is a common brown seaweed along the southeastern coast of China, playing a significant ecological role and possessing considerable resource utilization value. However, its genetic diversity and phylogeographic patterns remain poorly understood. In this study, we employed multiple molecular markers, including the nuclear ITS sequence (ribosomal internal transcribed spacer), the plastid rbcL gene (encoding the large subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase), and the mitochondrial cox3 and cox1 genes (encoding cytochrome c oxidase subunits III and I, respectively), to elucidate the genetic and phylogeographic structure of S. hemiphyllum var. chinense. Our findings demonstrate that the combined use of plastid and mitochondrial gene sequences is suitable for phylogeographic studies of this species. Genetic structure difference was observed among 15 populations which localities covering most of its distribution range, likely resulting from colonization by ancestors of different origins and limited gene flow among populations. The study revealed two distinct lineages of S. hemiphyllum var. chinense, exhibiting a north–south geographical distribution with a mixed zone in the southern Fujian–eastern Guangdong coastal region. These lineages are inferred to have diverged during the Middle to Late Pleistocene due to the isolation of the East China Sea and South China Sea during glacial periods. Sub-lineage differentiation was also detected within the northern lineage. The southern lineage experienced demographic expansion following the end of the Last Glacial Maximum, while the northern lineage remained stable. The southern Fujian–eastern Guangdong region, characterized by high genetic diversity, may have served as a glacial refugium or a contact zone for the post-glacial recolonization of the two lineages. Global warming may lead to range contraction and reduced genetic diversity in this species. The high genetic diversity area should be prioritized for conservation efforts. Overall, these findings provide insights into the genetic structure status and causes of S. hemiphyllum var. chinense and offer a scientific basis for proposing reasonable measures for its resource management.